The charcoal-fired blast furnaces of Scotland: a review - Lewis, John H (Proceedings of the Society of Antiquaries of Scotland, 1985)
Revises W I Macadam (1887), but concentrates on excavations at Red Smiddy, Glenkinglass, Tarrioch, and Bonawe. No evidence for ordnance at Red Smiddy; at Glenkinglass the blowing house had been river-eroded but the rest was fully excavated, while at Bonawe there was 19th century reorganization of mid-18th century works (blowing engine blocks intact).